Pendidikan Kesehatan Perilaku Hidup Bersih Sehat (PHBS) melalui Snake Ladder Game pada Kelompok Remaja - Lailaturohmah Kurniawati; Iyyana Al Fiatur Rofiiqoh; Khusnun Adma Hamidah (I-Com: Indonesian Community Journal, 2024)
Adolescents are vulnerable to various clean and healthy living behavior problems. Snake ladder game is one type of game in the form of a pawn board that is familiar among children to adolescents, so that with this method the preventive health message of PHBS can be conveyed according to the target, namely adolescents. This community service aimed to train the community on Clean Healthy Living Behavior (PHBS) through the Snake Ladder Game to a group of teenagers in Jebres, Surakarta. There are three stages in carrying out the series of activities: the preparation stage, the implementation stage, and the evaluation stage. The results of community service After counseling to respondents we gave several questions verbally about adolescent PHBS and several examples of delinquency in adolescents with a good level of knowledge, namely 92%. Conclusion There is an effect of increasing knowledge of Health Education on Clean Healthy Living Behavior (PHBS) through Snake Ladder Game in the Jebres Youth Group, Surakarta.